Pripravki granulocitov in priporočila za njihovo uporabo - Domanovič, Dragoslav (Zdravniški vestnik, 2011)
The use of granulocyte concentrate (GC) is usually the last therapeutic approach in patients with severe neutropenia, unresponsive to treatment with wide spectrum antibiotics and antimycotics. Because of the routine usage of granulocyte colony-stimulating factor, this therapeutic approach is nowadays more and more frequent and more effective. Therefore it is necessary to have an updated knowledge of this blood component. In the article, we present the whole process from collection and processing to treatment with GC.
Keywords: darovanje; granulociti; krvne bolezni; nevtrofilni granulociti; nevtropenija; pripravki; therapy; zdravljenje